Overexpression of IGFBP2 mRNA predicts poor survival in patients with glioblastoma. Issue 6 (14th June 2019) - Yuan, Qing; Cai, Hong-Qing; Zhong, Yi; Zhang, Min-Jie; Cheng, Zhi-Jian; Hao, Jia-Jie; Wang, Ming-Rong; Wan, Jing-Hai
Abstract : The prognosis of patients with glioblastoma (GBM) is dismal. It has been reported that Insulin-like growth factor (IGF) binding protein 2 (IGFBP2) is associated with the mobility and invasion of tumor cells. We investigated the expression of IGFBP2 mRNA in GBMs and its clinical relevance, using tissue microarrays and RNAscope in situ hybridization in 180 GBMs and 13 normal or edematous tissues. The correlations between the expression and clinical pathological parameters as well as some other biomarkers were analyzed. Overexpression of IGFBP2 mRNA was observed in 23.9% of tumors tested. No expression of IGFBP2 mRNA was detected in normal or edematous tissues. Kaplan–Meier survival analysis showed that the survival time of all the patients with high IGFBP2 tumors had shorter survival than those with low IGFBP2 ( P <0.01). Univariate regression and multivariate regression both indicated that the expression of IGFBP2 transcript level was an independent prognostic factor ( P =0.008 and 0.007, respectively). Furthermore, expression of IGFBP2 mRNA was related to the occurrence of isocitrate dehydrogenase 1 (IDH1) mutation, high heat shock protein 27 (Hsp27) expression and telomerase reverse transcriptase (TERT) promoter mutation (TERTp + ) ( P =0.013, 0.015 and 0.016, respectively), and patients with TERTp + /IGFBP2 high showed the shortest survival. In conclusion, IGFBP2 mRNA expression status is an independent prognostic biomarker in GBMs, and the combination of IGFBP2 mRNA and TERTp status might serve as a prognostic indicator in patients with GBM.